THE EFFECT OF COOPERATIVE LEARNING MODEL OF SNOWBALL THROWING TYPE ON THE PARTS OF BUILDING CONSTRUCTION MATERIAL TOWARD THE LEARNING RESULT OF THE Xth GRADE STUDENT’S TEKNIK GAMBAR BANGUNAN SMK NEGERI 1 PALANGKA RAYA - Benaumi Putri; Pantur Pandiangan; Tarita Aprilani Sitinjak (Jurusan Pendidikan Teknologi Dan Kejuruan, 2016)
The use Based on obsevation by doing interview with productive teacher show that learning approach which was implemented still use conventional method, that was discourse which commonly used although when completing the task discussion model was implemented among classmate only. It was because the teacher could not yet adjust himself with 2013 curriculum which just implemented of Xth grade student’s SMK Negeri 1 Palangka Raya. It couse learning process became monotonous and sends to be centered on the teacher only. So, by these problems, in this research cooperative learning of snowball throwing type was implemented to increase student’s learning result. The research using experiment quasi method by nonequivalent control group design research. The researchpopulation was whole the student of Teknik Gambar Bangunan grade X of SMK Negeri 1 Palangka Raya ini academic year 2014/2015 which amount 28 students consist of 16 students as experiment class and 12 students as control class was determined by the teacher of building contruction. The design approach that used ini this research kuantitative approach. This researc had done on November 2014. The data is taken from the data of student’s learning result. The result of the study showed that experiment group and control group work well (2,68 < 5,99) and the homogenoun (1,333 < 2,72). The average post test result of exsperiment group was 83,125 and control group was 68. The data technique analyze that used in this research was Uji-t, and based on the Uji-t calculation of the post test data showed that thitung 5,404 and ttabel 2,05 at 5% siqnifikansi level which mean thitung > ttabel (5,404 > 2,05). So H0 was refused and Ha was accepted. So, it can be concluded that the average student’s learning result on the parts of building construction material which taught by cooperative learning model of snowball throwing type was higher than the Student’s learning result which taught by discourse method. Therefore cooperative learnig model of snowball throwing type influenced the Student’s learning result on the part of building contruction material.